The Rhyacophila fasciata Species Complex (Trichoptera: Rhyacophilidae) in France and Switzerland, with description of a new species, Rhyacophila caussensis Valladolid & Coppa sp. nov. from France, based on morphological, genetic and ecological evidence - Valladolid, Maria; Arauzo, Mercedes; Coppa, Gennaro; Reding, Jean-Paul G.; Dorda, Beatriz A.; Rey, Isabel (Zootaxa, 2025)
The study of adult specimens belonging to the Rhyacophila fasciata Species Complex from mainland France has shown the presence of several different species: Rhyacophila denticulata McLachlan 1879 and Rhyacophila sociata Navás 1916 in the Pyrenees, Rhyacophila loeffleri Valladolid & Waringer 2023 in the northeast, and Rhyacophila septentrionis McLachlan 1865, widely distributed, mainly in the east. New data show that Switzerland harbours two species, R. septentrionis McLachlan 1865 in the Jorat region and western Jura Mountains and R. loeffleri Valladolid & Waringer 2023 in the remaining part of the country. A new species, Rhyacophila caussensis Valladolid & Coppa, sp. nov., from southeast France is described from male and female adults. We also present molecular mtCOI data, including novel sequences from specimens collected in France and Switzerland, and compare sequences of R. caussensis with corresponding data from R. fasciata, R. denticulata, R. sociata, R. loeffleri and R. septentrionis, as well as with the other species in the Complex: Rhyacophila kykladica Malicky & Sipahiler 1993, Rhyacophila delici Kučinić & Valladolid 2020, Rhyacophila viteceki Valladolid & Kučinić 2020, Rhyacophila macedonica Karaouzas, Valladolid & Ibrahimi 2022, and Rhyacophila anatolica Ekingen & Valladolid 2024. Our study revealed morphological differences between R. fasciata and R. caussensis, as well as genetic differences among the other taxa of the Rhyacophila fasciata Species Complex, supporting the recognition of R. caussensis as a new species.